A comparison study of Monosodium L-glutamate wastewater treatment by activated sludge process and biofilm process - BAI Xiao-hui; LI Gang; ZHONG Wei-guo (浙江大学学报. 农业与生命科学版)
After the pretreatment of ion-exchange wastewater by lime counteraction, heat by stream and aeration by air, two in-site pilot-scale experiments were performed to treat the Monosodium L-glutamate wastewater with activated sludge and biofilm separately. The experiment scale was 0.5 t/h. The characteristics of the mixed Monosodium L-glutamate wastewater after pretreatment were: COD; 1580-9510 mg/L, NH3-N: 108-2 270 mg/L. After one and half month experiment, two kinds of processes can get such a result: effluent COD<700 mg/L, effluent NH3-N<400 mg/L, removal rate of COD>90%, and NH3-N>80%. When the water temperature decreased, efficiency of the activated sludge process decreased and the effluent COD and NH3-N increased. However, performance of the aerobic process adding fixed biofilm was stable constantly, and the excess sludge released from the system was very little.